(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2015)
Nasopharyngeal carcinoma is a rare disease in children. It present with mass in the nasopharynx or neck swelling. Recently a six year old boy was diagnosed as a case of NPC and treated with standard chemotherapy. The boy was presented with neck swelling, palatal palsy and ear discharge. The patient was diagnosed by lymph node biopsy and immunohistochemistry. The diagnosis was delayed for 4 months which usually occur in our country. He was diagnosed by lymph node biopsy and immunohistochemistry. He was treated with standard protocol based chemotherapy. J. Paediatr. Surg. Bangladesh 4(1): 32-35, 2013 (January